Perencanaan Sarana dan Prasarana Pendidikan di SMK Negeri 1 Percut Sei Tuan - Usiono Usiono; Askur Amin; Samsir Damanik (Edumaspul: Jurnal Pendidikan, 2021)
In general, this study aims to describe the process of managing educational facilities and infrastructure at SMK Negeri 1 Percut Sei Tuan, in a context that focuses on planning educational facilities and infrastructure at SMK Negeri 1 Percut Sei Tuan. This study uses a qualitative research type, with a descriptive approach. The results of the study reveal that: Planning for facilities and infrastructure at SMK Negeri 1 Percut Sei Tuan is the initial stage in the management of facilities and infrastructure at the school, in that planning there is an entire process of carefully estimating the design of facility requirements needed by students, teachers and all staff at SMK Negeri 1 Percut Sei Tuan, including the purchase plan, procurement of rehabilitation, distribution and procurement of school equipment. Planning for educational facilities and infrastructure at SMK Negeri 1 Percut Sei Tuan is carried out through the following stages: (1) Accommodating all proposals for procurement of school equipment submitted by each department at SMK Negeri 1 Percut Sei Tuan. (2) Prepare a plan for school equipment needs for a certain period. (3) Conducting analysis and determining the priority scale of needs, (4) Integrating the needs plan with available school funds or budgets. (5) Determination of the plan for the procurement of facilities and infrastructure.